Relacionamento intergeracional entre idosos e adultos jovens da mesma família: caracterização e repercussões. - Silva, Cirlene Francisca Sales da (2019)
The main objective of this present thesis was to understand in which ways relationships between the elders and young adults of the same family happen, from their own perspectives. And, as specific objectives, facilitate the understanding of the complexity: 1) Describe the characteristics of the relationship between the elders and young adults; 2) Analyze how they perceive the influence between them; 3) Describe the positive and/or negative factors present in the relationship; 4) Indicate, from the participants' perception, what can be done to facilitate the relationship. These objectives permeated the whole thesis as a guiding line to clarify the problem. Thus, the thesis was organized in three articles/studies, which were oriented by themes and instruments that tried to enable a deeper understanding of how the relationships between elders and young adults of the same family occur, as follows: the first article, through a Systematic Review of the literature (2008-2018), aimed to understand the state of the art of the theme, more specifically the dialogues about the problem; the second, to understand from the view of twelve dyads composed by grandmothers-grandchildren, aunts-nephews, mothers-children, how they perceive the relationship between the two generations; and in the third, through the report of a Focal Group, composed of the same participants of the dyads in interaction, we sought to understand the relationship between the elders and young adults. The theoretical reference used to understand the phenomenon was the Systemic Thinking. It was used to analyze the studies, the qualitative method, cross-sectional cohort and with a sample for convenience. The instruments for data collection consisted of a sociodemographic questionnaire and a semi-structured interview script, which were answered individually at different times and places by the dyads composed of 12 elders and 12 young adults; in addition to the focus group, in which only seven elders and five young adults participated, which was performed in a single session. The results were evaluated through the Thematic Content Analysis Technique, composed by the pre-analysis, material exploration, treatment of the obtained results and interpretation. The main conclusions were: 1) there was a perception of distancing between the generations, which corroborates with the literature, although there is one member of each group, with whom one has more proximity; 2) among those who experience a closer relationship, there is a mutual influence; 3) as well as positive and negative factors in the relationship, as an example of positives: attention, care, affection, learning, trust, among others; and negatives: the lack of time of the younger, the use of technology, geographical distance, religion, family issues (tensions and conflicts), among others; 4) the strategies cited by the participants to facilitate the relationship were: to have a closer living experience, the young person could dedicate more time to the relationship, seek to understand and respect differences, among others. It was also pointed out that there is a lack of studies on the relationship between the elders and young adults of the same family, especially of aunts and uncles; another interesting finding was that most of the participants preferred paternal relatives (grandparents, uncles, aunts), the affinity/affective choice, referred to by two dyads, standing out to the blood tie, and a greater proximity between grandparent-grandchildren, as opposed to mothers-children or uncles/aunts-nephews. It was concluded from the results listed that, in order to minimize distancing between the enerations, that is, to "bring closer those farthest away", it is necessary, as a more immediate measure, the implementation of Programs and intergenerational encounters, which contribute to promoting rapprochement between generations. On the other hand, it is an imperative to teach people, from childhood on, to respect, welcome, understand, care for and love the elders, given their vulnerability in old age. Ideally, these teachings should transpose the domestic walls and be part of the school curriculum, in an effort to deconstruct the social stigma that places the older person in the place of disposable and social weight in some societies. Finally, it is hoped to give social and scientific visibility to the importance of the relationship between these generations, to provide theoretical and practical support to professionals working with this public, encouraging further research on the issues raised, in an effort to contribute to intergenerational solidarity.